PERAN PSIKOLOGI MASSA BAGI PEMBIMBING IBADAH HAJI - Nazia Nuril Fuadia (Balai Diklat Keagamaan Jakarta, 2020)
The role of psychology of mass communication is very important in developing the competence of Hajj supervisors and improving professionalism as a Hajj guide. In this scientific article the writer formulates a problem, how the Hajj supervisor can increase his competence in carrying out guidance activities. The purpose of this paper is to describe the role of mass psychology in increasing the professionalism of the Hajj pilgrimage guides which have an impact on the success of the implementation of the Hajj. Furthermore, the results of the analysis of the role of mass communication psychology also describe the importance of understanding the mass psychology of the pilgrims in the effectiveness of communication between the congregation and their supervisors so that the objectives of the communication can be achieved properly.